2015
DOI: 10.1007/s11084-015-9467-9
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Biomarkers from Cyanobacteria Mixed with Mars­Like Regolith Under Simulated Martian Atmosphere and UV Flux

Abstract: The space mission EXPOSE-R2 launched on the 24th of July 2014 to the International Space Station is carrying the BIOMEX (BIOlogy and Mars EXperiment) experiment aimed at investigating the endurance of extremophiles and stability of biomolecules under space and Mars-like conditions. In order to prepare the analyses of the returned samples, ground-based simulations were carried out in Planetary and Space Simulation facilities. During the ground-based simulations, Chroococcidiopsis cells mixed with two Martian mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 82 publications
2
37
0
Order By: Relevance
“…A great deal of interest in astrobiology has recently been devoted to different biomolecules, including DNA, to establish a suitable biosignature. Recent studies have proved the persistence of both carotenoids and DNA to polychromatic UV irradiation (Baqué et al, 2016), while eukaryotic DNA remained well detectable after both polychromatic UV irradiation and cosmic rays in real space conditions (Onofri et al, 2015;Pacelli et al, 2016). The STARLIFE project (Moeller et al, 2017, in this issue) aims to characterize the effect of ionizing radiation of astrobiological relevance on different microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of interest in astrobiology has recently been devoted to different biomolecules, including DNA, to establish a suitable biosignature. Recent studies have proved the persistence of both carotenoids and DNA to polychromatic UV irradiation (Baqué et al, 2016), while eukaryotic DNA remained well detectable after both polychromatic UV irradiation and cosmic rays in real space conditions (Onofri et al, 2015;Pacelli et al, 2016). The STARLIFE project (Moeller et al, 2017, in this issue) aims to characterize the effect of ionizing radiation of astrobiological relevance on different microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that organic molecules are quickly degraded under simulated Mars UV conditions (Baqué et al, ; Dartnell & Patel, ; Hintze et al, ; Poch et al, ; Stoker & Bullock, ; ten Kate et al, ). The destruction of the parent molecules occurs through the breaking of functional bonds, which creates radicals that can further damage the parent molecule (Ehrenfreund et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were pelleted (10,000g for 5 min), washed twice and resuspended in 20 mL of sterile double distilled water. DNA was extracted by performing 3 cycles of freeze-thawing (-80°C for 10 min and 60°C for 1 min) followed by 10 min boiling, as previously optimized (Baqué et al, 2016). After centrifugation (10,000g for 10 min), DNA concentrations were determined using the Qubit dsDNA HS Assay Kit and a Qubit 2.0 Fluorometer (Invitrogen).…”
Section: Genomic Pcr Fingerprintingmentioning
confidence: 99%